2019
DOI: 10.31533/pubvet.v13n4a309.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, laboratory and pathological characterization of naturally occurring equine botulinum toxin

Abstract: Horses are considerably more sensitive to ophidian venom compared to other species of domestic animals. The objective of this study was to characterize the clinical, laboratory and pathological findings of an equine treated at the University Veterinary Hospital Prof. Dr. Ivon Macêdo Tabosa of the Federal University of Campina Grande - Campus Patos - PB, afflicted by botrópico accident. As in most cases the snake involved cannot be visualized the diagnosis depends, fundamentally, on the prior knowledge of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Magalhães (2019) also reported the presence of thrombocytopenia and leukocytosis with left-shifted neutrophilia and mild anemia in humans in the first few hours after the bite. In a case report, Tolentino et al (2019) observed the presence of liver coagulation disorders (thrombocytopenia, hemorrhage, and increased blood coagulation time; decrease in albumin and globulin) and muscle damage (considerable increase in lactate dehydrogenase and creatine kinase), partially corroborating the findings of our experiment.…”
Section: Discussionsupporting
confidence: 90%
“…Magalhães (2019) also reported the presence of thrombocytopenia and leukocytosis with left-shifted neutrophilia and mild anemia in humans in the first few hours after the bite. In a case report, Tolentino et al (2019) observed the presence of liver coagulation disorders (thrombocytopenia, hemorrhage, and increased blood coagulation time; decrease in albumin and globulin) and muscle damage (considerable increase in lactate dehydrogenase and creatine kinase), partially corroborating the findings of our experiment.…”
Section: Discussionsupporting
confidence: 90%